Context Dependent Role of Type 2 Innate Lymphoid Cells in Allergic Skin Inflammation - Rafei-Shamsabadi, David A.; Klose, Christoph S. N.; Halim, Timotheus Y. F.; Tanriver, Yakup; Jakob, Thilo (Frontiers in Immunology, 2019)
The discovery of innate lymphoid cells (ILC) has profoundly influenced the understanding of innate and adaptive immune crosstalk in health and disease. ILC and T cells share developmental and functional characteristics such as the lineage-specifying transcription factors and effector cytokines, but importantly ILC do not display rearranged antigen-specific receptors. Similar to T cells ILC are subdivided into 3 different helper-like subtypes, namely ILC1-3, and a killer-like subtype comprising natural killer (NK) cells. Increasing evidence supports the physiological relevance of ILC, e.g., in wound healing and defense against parasites, as well as their pathogenic role in allergy, inflammatory bowel diseases or psoriasis. Group 2 ILC have been attributed to the pathogenesis of allergic diseases like asthma and atopic dermatitis. Other inflammatory skin diseases such as allergic contact dermatitis are profoundly shaped by inflammatory NK cells. This article reviews the role of ILC in allergic skin diseases with a major focus on ILC2. While group 2 ILC are suggested to contribute to the pathogenesis of type 2 dominated inflammation as seen in atopic dermatitis, we have shown that lack of ILC2 in type 1 dominated contact hypersensitivity results in enhanced inflammation, suggesting a regulatory role of ILC2 in this context. We provide a concept of how ILC2 may influence context dependent the mutual counterbalance between type I and type II immune responses in allergic skin diseases.